IMPLEMENTING ICT-BASED PHONOLOGY LEARNING MATERIAL USING BLENDSPACE THROUGH CLASSROOM ACTION RESEARCH - Adnyani, Ni Luh Putu Sri; Sari, Rima Andriani; Suputra, Putu Eka Dambayana; Pastika, I Wayan; Suparwa, I Nyoman (Balai Bahasa Bali, 2018)
This study reports the implementation of ICT-based learning materials using Blendspace in phonology classes. The ICT-based learning material was developed in the academic year of 2016/2017. The study was conducted in two stages. The rst stage was the validation of the teaching material by two expert judges. The second stage was trying out of the teaching material in the classroom using classroom action research. The learning material developed has been validated by experts using a checklist as an instrument, which has been analysed using the Gregory formula. The expert judges showed that the content validity of the learning material is 90.9%, which means very valid. In order to test the effectiveness of the learning material, it has been implemented in phonology classes joined by the second-semester Diploma III students of the English Department of Universitas Pendidikan Ganesha, using classroom action research. Based on the teaching and learning process using the material, more than 70% of the students obtained scores between 76 and 100. Fewer than 30% of the students had scores below 75. Therefore, the learning material is considered effective for learning phonology.